Endometrial polyp removed by a manual hysteroscopic tissue removal device - Menelik Man Hin Lee (Wolters Kluwer Medknow Publications, 2020)
We report one of the first cases where an endometrial polyp was removed using a manual hysteroscopic tissue removal (HTR) device. The case showed its feasibility with potential reduction in the required setup time and tubing required compared to routine HTR device. This technique is ideal in the removal of endometrial polyps, particularly within the outpatient settings.